KEHIDUPAN SOSIAL BUDAYA ETNIS TIONGHOA DI KOTA MANADO - Rasyid, Haris; Matheosz, Jenny Nelly; Deeng, Djefry (HOLISTIK, Journal Of Social and Culture, 2021)
Indonesian culture although diverse but formed and influenced by other major cultures such as Chinese culture, Indian culture and Arab culture. China is part of the diversity of the Indonesian nation that existed long before independence, the presence of Chinese people in Indonesia seems to have been united and become an integral part of the life of the Indonesian nation that also has horizontal conflicts with indigenous people and there is discrimination against ethnic Chinese or Chinese. For people of Chinese descent born and raised in North Sulawesi, they live in a mix with local residents. Not a few who bear the name of the family Minahasa. In addition to the physical appearance and skin color that is similar to the citizens of Minahasa. The unique social system has supported them to blend in with the population in Manado, and with expertise in terms of trade has made them dominate the local to national economy. With great capital, Confucian teachings, native Chinese and crossbreed Chinese have played an important role as economic drivers in Manado. It is noted that ethnic Chinese who work as traders / business or plunge in politics and government.Likewise, their indigenous culture has been able to adapt to the local culture of Manado to add the diversity of cultures that develop in the city of Manado. The Chinese culture includes the kinship system, the diversity of languages of each ethnic Chinese tribe, their Religion / Religion that is Tridarma, places of worship / temples rich in architecture, lunar celebrations, and lively barongsai performances.Keywords: Chinese, socio-cultural, mingling